The Central European Theatre of Cold War Struggles in the Feature Films of the Third Polish Republic - Radoslaw Domke (Codrul Cosminului)
This article examines several Polish film productions that contain geopolitical codes, thus allowing an interpretation of the Cold War confrontations on the Central European stage from the perspective of Poland's filmography after 1989. Russians portray the antagonistic characters in these films, especially Soviet communist dignitaries, whether civilian or military. In contrast, Americans and other “defenders of democracy” in the Western sense of the term become the positive heroes. Thus, geopolitical codes – clearly identified – can indicate how the soft power actions of the United States of America contributed to the consolidation of a distinct image in Poland.